Impact of Hypertension on Iraqi Diabetic Patients According to The Age and Sex - Ammal Esmaeel Ibrahim, Saba hamid (Drugs and Cell Therapies in Hematology, 2021)
Hypertension distinct as a blood pressure further than140/90 mmHg is an tremendously public illness in diabetes, touching ∼20-60% of patients with diabetes, reliant on age, obesity, and ethnicity. Hypertension is a disorder in which blood pressure is in elevation. This study was completed through the period from September till December 2016. This study contains three hundred patients with diabetes mellitus were let in to Outpatient clinic at the national diabetes center/ AL-Mustansiriya university. Patients with age rang (30-84) years old were involved in this study. Diabetes and Hypertension are in mutual aid therefore, cultivate consecutively in the same patients.